Effects of Lithium Salt Addition Methods on the High-Temperature Electrochemical Performance of LiMn2O4. Issue 9 (2nd September 2021) - Chaolian, Huang; Ruibo, Zhang; Yike, Gao; Xiaoying, Lu; Qi, Jiang; Hong, Zhang; Zhicheng, Li
Abstract : The poor high-temperature stability of spinel LiMn2 O4 cathode material has become a bottleneck hindering its large-scale application. To enhance its high-temperature electrochemical performance, the effects of two different methods of lithium salt addition on its high-temperature electrochemical performance were studied. Two methods, Li + infiltration and solid phase mixing, were used to prepare spinel LiMn2 O4 cathode material by the same high-temperature solid phase method, respectively. The obtained materials were characterized by X-ray diffraction, scanning electron microscopy, Raman, and particle size analysis. Electrochemical performance tests were carried out on the electrochemical equipment by assembling into a half-battery. The results show that the material obtained by the lithium salt solid phase mixing method presents a loose structure composed of small primary particles to form a spherical secondary particle. However, the material obtained by the Li + infiltration method presents an octahedral crystal structure, showing a trend toward single crystal. At the same time, its calcination time is greatly shortened (from 26 to 6 h) at the same calcination temperature. The electrochemical performance test results at 55 °C show that the LiMn2 O4 prepared by Li + infiltration has a better high-temperature electrochemical performance.